SPECTRUM OF PERFORATION PERITONITIS IN WESTERN NEPAL - Poudel, Rajesh; Shah, Santosh; Chandra, Kailash; Pradhan, Saroj; Joshi, Pravin (Journal of Universal College of Medical Sciences, 2018)
Introduction: Despite advances in surgical technique, antimicrobial therapy and perioperative care morbidity and mortality in perforated peritonitis is still high. Aim of this study was to highlight the clinical presentation, intra operative findings and postoperative complications and mortality among patient who has undergone emergency surgery for perforated peritonitis in tertiary care center in western Nepal. Materials and Methods: This was a retrospective descriptive study carried out in Universal College of Medical Sciences, Bhairawha, Nepal. All patients who underwent emergency exploratory laparotomy for perforated peritonitis in one year period (from April 2014 to March 2015) were included in the study. Results: Total 90 cases met inclusion criteria and were analyzed. Most common presenting symptom was pain abdomen. Pneumoperitoneum was seen in 86 (95.6%) patients. Most common site of perforation was prepyloric perforation followed by duodenum. Most common cause of perforation was Acid peptic disease. Most common surgical procedure performed was Omentopexy. There were total of 11 (12.2%)mortality. Conclusion: The spectrum of perforation peritonitis in our study differs from western countries whereas it is similar to that of other research from Indian subcontinent. Majority of perforations are noticed in the duodenum and stomach due to acid-peptic disease and small bowel typhoid followed by trauma. Overall mortality was seen in 12.2%. Journal of Universal College of Medical Science Vol. 6, No. 1, 2018, Page: 11-13